Locked-in Syndrome Post Facet Joint Injection: A Case Report - Muhamad Rafiqi Hehsan; Suki Ismet; Shamsul Kamalrujan Hassan; Kamaruddin Ibrahim (Anaesthesia, Pain & Intensive Care, 2024)
Indexed by WOS/ Scopus